Differences in Mathematical Communication Ability Using Discovery Learning and Conventional Learning Models - Widyanti Astari; Slamet Soro (Universitas Negeri Makassar, 2022)
The aims of this research to see the differences in mathematical communication ablility using discovery learning models and conventional learning models and see whether the use of discovery learning models and conventional learning models affects students' mathematical communication abilities. The sample of this research was 70 learners from two different classes who were randomly selected with purposive sampling techniques. The selected class is used as an experimental class using the discovery learning model and other classes as a control class using a conventional learning model. The data in this research were obtained from the results of the initial test and the final test of mathematical communication ability carried out before and after learning. The data will be analyzed using homogeneity test, normality test, independent sample T-test and paired T-test. The research conducted shows that: (1) The learning model applied to each class can have an influence on mathematical communication abilities. This is evidenced by the increase in the final test results given after learning (2) a learning model that allows students to actively participate in learning activities is not necessarily better than conventional learning models. This is shown by the similarity between the final test scores of the experimental class and the control class.